Diagnosis of Bovine Tuberculosis at Slaughterhouses - Osei-Agyemang, B. (University of Ghana, 2001)
Cattle infected with Mycobacterium bovis, the causative agent of bovine tuberculosis (BTB), an important zoonotic disease, can be identified by a range of tests on live animals as well as at post mortem. Post mortem inspection often fails to detect early cases where lesions have not yet developed, cases where lesions are present in organs or parts of the carcass, which are not routinely examined, or in cases where the lesions are confused with those due to other infectious agents. The present study was designed to test the specific hypothesis that “pimply gut-like lesions found in the intestines of cattle at meat inspection are largely due to BTB and not the gut worm, Oesophagostomum, and are missed at meat inspection, posing substantial risk to human infection. In a prospective, double-blinded experiment, 150 cattle were sent for slaughter and meat inspection, after they had tested for BTB using the BTB-specific comparative tuberculin test (CTT). Seventy-five out of the one hundred and fifty cattle (50%) were tuberculin test positive, with an equal number negative. At slaughter, meat inspection was performed as recommended by the Ghana meat inspection act, 1962. and records of post mortem findings for individual animals were carefully recorded. Tissue samples were also taken to the laboratory for detailed examination. Detailed examination involved slicing of organs at 2-mm interval and examination for the presence of tuberculosis lesions. Smears from the lesions were stained and microscopically examined for the presence of acid-fast bacilli. The detailed post-mortem meat inspection investigation carried out revealed the presence of small, round nodular (raised) lesions, of diameter 0.01-to 0.5cm,often referred to as “pimply gut” by the meat inspectors, exclusively in the intestines of all the seventy-five cattle that tested positive to tuberculin test prior to slaughter. Microscopic examination of these lesions in the laboratory revealed the presence of acid-fast bacilli in 77.7% of the cattle. Of the one hundred and fifty animals with known tuberculin status (seventy five tuberculin positive and seventy five tuberculin negative) slaughtered, only one was suspected of having bovine tuberculosis by meat inspectors. Seventy-four out of the seventy-five (98.7%) cattle that tested positive by CTT were passed as bovine tuberculosis negative and so fit for human consumption. The causative organism of BTB, M bovis is an acid-fast bacillus. Although the acid fast organisms present in the “pimply gut-like” lesions were not specifically identified, taken together with strong association between tuberculin positive reaction and the presence of these lesions, it can be concluded that animals that tested positive to tuberculin test were indeed infected with the bovine tuberculosis. The high percentage of lesions found in the intestines of BTB positive cattle confirms that, in Africa, including Ghana, water and feed for cattle are likely to be contaminated with M bovis, making the oral route of infection a most important means by which BTB is spread. In the developed countries, where water and feed are almost free from M bovis, aerosol may be the common route by which BTB is spread. Hence the lungs and associated organs are considered to be the points for BTB lesions. The results of the present study provide explanation for the very large percentage of tuberculin positive test animals without lesions and. reveals that meat inspection may not be effective in diagnosis of BTB in Ghana. Lack of training and poor facilities further makes meat inspection less effective. Further work is required to isolate and type the acid-fast bacilli identified and to help formulate programmes for the control of BTB in Ghana. The study further recommends the training of Meat Inspectors and provision of logistics.
Thesis(MPH)-University of Ghana, 2001